The Formation of Highly Positive δ34S Values in Late Devonian Mudstones: Microscale Analysis of Pyrite (δ34S) and Barite (δ34S, δ18O) in the Canol Formation (Selwyn Basin, Canada) - Grema, Haruna M.; Magnall, Joseph M.; Whitehouse, Martin J.; Gleeson, Sarah A.; Schulz, Hans-Martin (Frontiers in Earth Science, 2022)
The sulfur isotope composition of pyrite in marine sedimentary rocks is often difficult to interpret due to a lack of precise isotopic constraints for coeval sulfate. This study examines pyrite and barite in the Late Devonian Canol Formation (Selwyn Basin, Canada), which provides an archive of δ34S and δ18O values during diagenesis. Scanning electron microscopy (SEM) has been combined with microscale secondary ion mass spectrometry (SIMS) analysis (n = 1,032) of pyrite (δ34S) and barite (δ34S and δ18O) on samples collected from nine stratigraphic sections of the Canol Formation. Two paragenetic stages of pyrite and barite formation have been distinguished, both replaced by barium carbonate and feldspar. The δ34Sbarite and δ18Obarite values from all sections overlap, between +37.1‰ and +67.9‰ (median = +45.7‰) and +8.8‰ and +23.9‰ (median = +20.0‰), respectively. Barite morphologies and isotopic values are consistent with precipitation from diagenetically modified porewater sulfate (sulfate resupply << sulfate depletion) during early diagenesis. The two pyrite generations (Py-1 and Py-2) preserve distinct textures and end-member isotopic records. There is a large offset from coeval Late Devonian seawater sulfate in the δ34Spyrite values of framboidal pyrite (-29.4‰ to -9.3‰), consistent with dissimilatory microbial sulfate reduction (MSR) during early diagenesis. The Py-2 is in textural equilibrium with barite generation 2 (Brt-2) and records a broad range of more positive δ34SPy-2 values (+9.4‰ to + 44.5‰). The distinctive highly positive δ34Spyrite values developed from sulfate limited conditions around the sulfate methane transition zone (SMTZ). We propose that a combination of factors, including low sulfate concentrations, MSR, and sulfate reduction coupled to anaerobic oxidation of methane (SR-AOM), led to the formation of highly positive δ34Spyrite and δ34Sbarite values in the Canol Formation. The presence of highly positive δ34Spyrite values in other Late Devonian sedimentary units indicate that diagenetic pyrite formation at the SMTZ may be a more general feature of other Lower Paleozoic basins.